The Effect of Two Stay Two Stray In Toward Students’ Self-Esteem - Titik Ceriyani Miswaty (STKIP PGRI Tulungagung, 2021)
This research was aimed at find out whether or not using Two Stay Two Stray effective in toward students’ Self-Esteem in speaking. The research was quasi experimental research with nonequivalent control group design. The population of the study was second grade students of SMPN 3 Batukliang which was consisted of two classes. Two classes were chosen as the samples by using population sampling technique; those were VIII A as experimental class was treated by using Two Stay Two Stray, and VIII C as control class was treated by using One Stray Three Stay, they were chosen by used lottre. The instrument to collect the research data. The scores were analyzed by using descriptive and inferential analysis, descriptive analysis used to describe mean, mode, median and standard deviation both of group, and the inferential analysis is to describe the value of t-test for the comparison between t-table. It shows that the value of t-test = 2,53 was higher than the value of t-table = 1,688 as the level of significance of 0,05% and the number of df (36). Therefore, based on the result of the analysis, it can be concluded that there is significant difference between students’ Self-Esteem scores taught by Two Stay Two Stray. In other words, Two Stay Two Stray has positive effect toward students’ in Self-Esteem.